2021
DOI: 10.1002/ehf2.13563
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of new‐onset atrial fibrillation in patients with hypertrophic cardiomyopathy

Abstract: Aims There is limited information about the clinical significance of atrial fibrillation (AF), particularly new‐onset AF, in patients with hypertrophic cardiomyopathy (HCM) in a community‐based patient cohort. This study was carried out to clarify the prevalence and prognostic impact of AF in Japanese HCM patients. Methods and results In 2004, we established a cardiomyopathy registration network in Kochi Prefecture as a prospective study, and finally, 293 patients with HCM were followed. In the patients' cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…1 Data on AF in patients with HCM published since the 2020 hypertrophic cardiomyopathy guideline were reviewed but did not result in any substantive changes in the recommendations from 2020. 2–6 AF is highly prevalent in HCM and increases the risk of stroke. The CHA 2 DS 2 -VASc score should not apply to patients with HCM, because they have roughly an equivalent risk to a CHADs-VASc of 3.…”
Section: Af and Specific Patient Groupsmentioning
confidence: 99%
“…1 Data on AF in patients with HCM published since the 2020 hypertrophic cardiomyopathy guideline were reviewed but did not result in any substantive changes in the recommendations from 2020. 2–6 AF is highly prevalent in HCM and increases the risk of stroke. The CHA 2 DS 2 -VASc score should not apply to patients with HCM, because they have roughly an equivalent risk to a CHADs-VASc of 3.…”
Section: Af and Specific Patient Groupsmentioning
confidence: 99%
“…The current study demonstrated that LVDs and AF (paroxysmal, persistent, or chronic) before enrollment were significant predictors of DHCM. Many studies [4,[16][17][18][19][20] have reported the importance of AF in patients with HCM. AF increases the risk of heart failure, stroke, and sudden death [4,17,20].…”
Section: Discussionmentioning
confidence: 99%
“…LV end-diastolic dimension (mm) 44 [40][41][42][43][44][45][46][47][48] LV end-systolic dimension (mm) 27 [23][24][25][26][27][28][29][30] LVEF (%) 60.5±4.5…”
Section: Echocardiography (N=330)unclassified
“…Other abbreviations as in Table1.development of LVSD) simultaneously in a single cohort. Several previous studies have reported predictors of HF hospitalization in HCM; however, no study has focused on LVEF at hospitalization, or other studies considered HF hospitalization as a part of a composite endpoint [23][24][25][26][27][28][29][30]. Some studies have reported progression of NYHA func-predictors and a small overlap, as well as different risk factors from SCD.…”
mentioning
confidence: 99%